2015
DOI: 10.11648/j.ajns.20150403.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses’ Perceptions and Barriers on Evidence Based Practice in Tikur Anbessa Specialized Hospital Addis Ababa Ethiopia

Abstract: Background: Historically, nurses have relied on expert' opinions in clinical decision-making. However, these ways of practicing may not only be outdated but unsafe. Experienced-based knowledge may be associated with biased thinking that lead to errors. Objective: Assessment of nurses' perceptions, level of use and barriers on Evidence Based Practice. Method: Two hundred ten nurses were assessed through self-administer questionnaires for quantitative and fifteen nurses were also involved in in-depth interview f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
59
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 62 publications
24
59
5
Order By: Relevance
“…These findings agree with earlier studies (Hadgu et al, 2015;Okwundu, 2010;Nwagwu, 2008) that found inadequate EBM knowledge and training in health workers. Our study also reveled that almost all (97%) academics were interest in EBM training consistent with other authors (McInerney & Suleman, 2010;Okwundu, 2010;Hadgu et al, 2015). While we cannot give authentic reasons for these results, EBM training courses could be limited in Namibia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings agree with earlier studies (Hadgu et al, 2015;Okwundu, 2010;Nwagwu, 2008) that found inadequate EBM knowledge and training in health workers. Our study also reveled that almost all (97%) academics were interest in EBM training consistent with other authors (McInerney & Suleman, 2010;Okwundu, 2010;Hadgu et al, 2015). While we cannot give authentic reasons for these results, EBM training courses could be limited in Namibia.…”
Section: Discussionsupporting
confidence: 93%
“…The majority (89%) had favorable views of EBM, consistent with academics study by McInerney & Suleman (2010). The presence of positive attitudes towards EBM was also consistent with the findings of other authors in in Africa (Boer, 2012;Ntaganira, 2012;Hadgu et al, 2015). In this study, the majority (66%) reported EBM promotion in their institution, which supports a previous finding in South African University (McInerney & Suleman, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…EBP stipulates the use of current best evidence with clinical experiences and patient preferences to make sound decisions regarding patient care [3]. During the past two decades, the principle of EBP has been used outside the field of medicine, including nursing [4][5][6][7][8], mental health [9], population health [2], higher education [10] and policy development [11].…”
Section: Introductionmentioning
confidence: 99%
“…These barriers can be broadly classified as organizational, individual and peer level barriers [20]. In Africa, few such studies have explored the barriers of EBP in public health system and higher education sector [6,7,10,14,[22][23][24][25][26][27][28][29], but none in the military healthcare system. Thus far, evidence is lacking on the relevance and barriers to EBP in military healthcare in Africa.…”
Section: Introductionmentioning
confidence: 99%